2013
DOI: 10.1007/s12350-013-9679-1
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of adjunctive regadenoson injection at peak exercise during exercise myocardial perfusion imaging: The Both Exercise and Regadenoson Stress Test (BERST) trial

Abstract: Background. The data existing in the literature regarding the safety of using regadenoson with symptom-limited exercise are limited, which motivated the authors to undertake this randomized study.Methods. We offered patients scheduled to undergo vasodilator stress nuclear myocardial perfusion imaging the opportunity to exercise instead. Patients who failed to reach target heart rate (THR) were randomized to (1) receive regadenoson at peak exercise or (2) stop exercise and receive regadenoson at rest. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…[18][19][20][21] Regadenoson administration has been studied at peak exercise holding the maximally attained stage, at reduced exercise, during walk recovery, and at rest. While two of the studies found no differences in the safety and side-effect profile based on the time of regadenoson administration, one study suggested more exaggerated BP responses when administered at peak exercise.…”
mentioning
confidence: 99%
“…[18][19][20][21] Regadenoson administration has been studied at peak exercise holding the maximally attained stage, at reduced exercise, during walk recovery, and at rest. While two of the studies found no differences in the safety and side-effect profile based on the time of regadenoson administration, one study suggested more exaggerated BP responses when administered at peak exercise.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] Pharmacologic stress has also been combined with symptom-limited exercise in suitable patients as a means to obtain valuable functional data while ensuring adequate stress. [7][8][9][10][11][12] Since its approval in 2008, regadenoson has become the most commonly used vasodilator used in pharmacologic perfusion imaging surpassing adenosine and dipyridamole. 13 Although it involves an off-label use of the agent, interest and experience in protocols combining symptom-limited exercise and pharmacologic stress is increasing.…”
Section: See Related Article Pp 34-40mentioning
confidence: 99%
“…Studies to date have shown that combining regadenoson with some form of exercise is feasible and safe. 5,6,[9][10][11][12] However, some patients we intend to stress with regadenoson cannot walk on a treadmill. What can we do for these patients to enhance their experience and improve image quality?…”
Section: See Related Article Pp 34-40mentioning
confidence: 99%
“…Several studies consistently showed less side effects from regadenoson with an adjunctive exercise protocol even in comparison with regadenoson-only. [21][22][23][24][25] To optimize the use of regadenoson plus exercise protocols, regadenoson can be adjunctively administered for selected patients who could not achieve a maximal predicted heart rate during exercise. In terms of diagnostic feasibility, the most recent prospective study, the EXERRT trial 24 found non-inferior diagnostic agreements of regadenoson at an early recovery phase from submaximal exercise as compared to regadenoson stress only at 1 hour after full recovery from submaximal exercise.…”
mentioning
confidence: 99%
“…Although the hemodynamic efficacy for optimal assessment of stress myocardial perfusion seems somewhat suboptimal, recent studies in various imaging modalities encourage the use of regadenoson as a competent stress agent in the diagnosis of coronary artery disease. 20,21 Regadenoson at peak exercise 22 Regadenoson ? peak or low-level exercise 23 Adjunctive regadenoson for submaximal exercise 24 Invasive measures New pharmacologic agent IC nicorandil 11 Omitting vasodilatory stress iFR 13,14 MPI, myocardial perfusion imaging; IC, intra-coronary; iFR, instantaneous wave-free ratio a Adjunctive exercise protocols were grouped following the classification by Mahmarian 25 …”
mentioning
confidence: 99%